Disentangling Social-Genetic From Rearing-Environment Effects for Alcohol Use Disorder Using Swedish National Data - Salvatore, Jessica E. (Psychol Sci, 2020)
Investigations of social-genetic effects, whereby a social partner’s genotype affects another’s outcomes, can be confounded by the influence of the social partner’s rearing environment. We used marital information on more than 300,000 couples from Swedish national data to disentangle social-genetic from rearing-environment effects for alcohol use disorder (AUD). Using observational and extended-family designs, we found that (a) marriage to a spouse with a predisposition toward AUD (as indexed by a parental history of AUD) increased risk for developing AUD; (b) this increased risk was not explained by socioeconomic status, the spouse’s AUD status, or contact with the spouse’s parents; and (c) this increased risk reflected the psychological consequences of the spouse having grown up with an AUD-affected parent (i.e., a rearing-environment effect) rather than a social-genetic effect. Findings illustrate that a spouse’s rearing-environment exposures may confer risk for AUD.